Prognostic significance of KIT exon 11 deletion mutation in intermediate‐risk gastrointestinal stromal tumor. Issue 3 (17th October 2016) - Quek, Richard; Farid, Mohamad; Kanjanapan, Yada; Lim, Cindy; Tan, Iain Beehuat; Kesavan, Sittampalam; Lim, Tony Kiat Hon; Oon, Lynette Lin‐Ean; Goh, Brian KP; Chan, Weng Hoong; Teo, Melissa; Chung, Alexander YF; et al.
Abstract: Aim: Benefit of adjuvant imatinib therapy following curative resection in patients with intermediate‐risk gastrointestinal stromal tumor (GIST) is unclear. GIST‐specific exon mutations, in particular exon 11 deletions, have been shown to be prognostic. We hypothesize that specific KIT mutations may improve risk stratification in patients with intermediate‐risk GIST, identifying a subgroup of patients who may benefit from adjuvant therapy. Methods: In total, 142 GIST patients with complete clinicopathologic and mutational data from two sites were included. Risk classification was based on the modified National Institute of Health (NIH) criteria. Results: In this cohort, 74% ( n = 105) of patients harbored a KIT mutation; 61% ( n = 86) were found in exon 11 of which nearly 70% were KIT exon 11 deletions ( n = 60). A total of 18% ( n = 25) of cases were classified as having intermediate‐risk disease. Univariate analysis confirmed tumor size, mitotic index, nongastric origin, presence of tumor rupture and modified NIH criteria were adversely prognostic for relapse‐free survival (RFS). Among KIT/PDGFRA mutants, KIT exon 11 deletions had a significantly worse prognosis (hazard ratio 2.31; 95% confidence interval, 1.30–4.10; P = 0.003). Multivariate analysis confirmed KIT exon 11 deletion ( P = 0.003) and clinical risk classification ( P < 0.001) as independent adverse prognostic factors for RFS. Intermediate‐risk patients harboring KIT exon 11 deletions had RFS outcomes similar to high‐risk patients. Conclusion: The presence of KIT exon 11 deletion mutation in patients with intermediate‐risk GIST is associated with an inferior clinical outcome with RFS similar to high‐risk patients.